2016
DOI: 10.1111/gcbb.12351
|View full text |Cite
|
Sign up to set email alerts
|

The impact of soil salinity on the yield, composition and physiology of the bioenergy grass Miscanthus × giganteus

Abstract: High salinity land may provide an alternative resource for the cultivation of dedicated biomass crops for renewable energy and chemicals, thus avoiding competition for land use with food crops. The commercial perennial grass Miscanthus 9 giganteus is a leading biomass crop; however, its response to salt stress is largely unknown. Miscanthus 9 giganteus was grown in pots irrigated with nine different NaCl concentrations (0, 2.86, 5.44, 7.96, 10.65, 14.68, 17.5, 19.97 and 22.4 dS m À1 ). Biomass yield was reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
77
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(89 citation statements)
references
References 62 publications
8
77
1
3
Order By: Relevance
“…The overwintering ability QTL on LG 4 (QTL id: OWA2) contained the osmotin gene OSM34 . Osmotin genes have been shown to induce proline accumulation that confers tolerance against both biotic and abiotic stresses in plants such as Miscanthus , tomato, strawberry, Arabidopsis, and olive trees (Abdin, Kiran, & Alam, ; D'Angeli & Altamura, ; Ings, Mur, Robson, & Bosch, ; Płażek et al, ; Stavridou, Hastings, Webster, & Robson, ). A QTL on Miscanthus LG 11 (QTL id: OWA6) encompassed two plausible candidate genes, carboxylesterase 13 ( CEX13 ) and WRKY transcription factor ( WRKY2 ), both of which were reported to be responsive to cold stress in Arabidopsis (Seki et al, ), grape ( Vitis amurensis ) (Xin et al, ), and Peruvian lily ( Alstroemeria ) (Wagstaff et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The overwintering ability QTL on LG 4 (QTL id: OWA2) contained the osmotin gene OSM34 . Osmotin genes have been shown to induce proline accumulation that confers tolerance against both biotic and abiotic stresses in plants such as Miscanthus , tomato, strawberry, Arabidopsis, and olive trees (Abdin, Kiran, & Alam, ; D'Angeli & Altamura, ; Ings, Mur, Robson, & Bosch, ; Płażek et al, ; Stavridou, Hastings, Webster, & Robson, ). A QTL on Miscanthus LG 11 (QTL id: OWA6) encompassed two plausible candidate genes, carboxylesterase 13 ( CEX13 ) and WRKY transcription factor ( WRKY2 ), both of which were reported to be responsive to cold stress in Arabidopsis (Seki et al, ), grape ( Vitis amurensis ) (Xin et al, ), and Peruvian lily ( Alstroemeria ) (Wagstaff et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, Karyotis et al (2003) indicated that the considerable seed yield loss under saline soil condition (6.5 dSm -1 ) was due to poor and uneven plant density caused by adverse soil properties such as high soil pH (pH 8.5) and poor aeration and water permeability. However, yield loss due to salinity stress is closely related to four major constraints: (1) water deficit, (2) ion toxicity, (3) nutrient imbalance, (4) restriction of CO 2 uptake (Marschner, 1995;Stavridou et al, 2016;Munns and Tester, 2008). Concerning the effect of salinity on quinoa plants, Eisa et al, (2012), reported that neither osmotic stress nor ion deficiency or toxicity appears to be determinant for C. quinoa under saline condition.…”
Section: Discussionmentioning
confidence: 99%
“…Marginal areas are unsuitable for the (economically) benign cultivation of traditional crops due to a range of potential factors such as moisture, salinity, temperature, soil depth or even field shape (Clifton‐Brown et al, ; Quinn et al, ). Moreover, it has been reported that miscanthus can be grown on heavy metal‐contaminated or saline soils (Nsanganwimana, Pourrut, Mench, & Douay, ; Pidlisnyuk, Stefanovska, Lewis, Erickson, & Davis, ; Stavridou, Hastings, Webster, & Robson, ; Sun, Yamada, & Takano, ). Considering these aspects, miscanthus cultivation could contribute to a sustainable biomass provision, reducing land use competition and improving the profitability of agricultural land of lower quality (Allison, Morris, Clifton‐Brown, Lister, & Donnison, ; Clifton‐Brown et al, ; Hu, Wu, Persson, Peng, & Feng, ).…”
Section: Introductionmentioning
confidence: 99%